Implementasi Inverter Pada Distribusi Air Di Perumdam Tirta Tarum Karawang - Amani, Muhammad Rafi Zaki; Lammada, Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2025)
Clean water is an essential requirement for human life, yet challenges such as declining water quality due to pollution and climate change demand effective solutions. Perumdam Tirta Tarum Karawang plays a crucial role in providing clean water through a treatment system that includes intake pumps, Water Treatment Plant (WTP), sedimentation, filtration, and distribution pumps. In efforts to maintain operational sustainability and efficiency, the focus is on using inverters for distribution pumps. Inverters are employed to control the speed and electrical current required, reducing energy consumption and adjusting output to meet demand. The implementation of inverters is expected to enhance operational efficiency while lowering production costs, ensuring the sustainability of water resources, and supporting environmental conservation efforts